Penerapan Model Problem Based Learning (Pbl) Untuk Meningkatkan Hasil Belajar Bahasa Indonesia Kelas IV SD Inpres Perumnas Uluindano Tomohon - Toisi, Dyah Putri Cahyani; Rorimpandey, Widdy H.; Kaunang, Magdalena J. (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to improve the Indonesian language learning outcomes of class IV students at Perumnas Uluindano Tomohon through a problem based learning model on the sub-theme Me and My Dreams, a classroom action research method, which consists of planning, implementation, observation, reflection. The research subjects were fourth grade students at SD Inpres Perumnas Uluindano. Data analysis techniques are tests and observations. The research results showed that the achievement in cycle I was 58.5% and in cycle II the results achieved were 84.5%. It can be concluded that the application of the problem based learning model can improve student learning outcomes in Indonesian language subjects in the material Me and My Dreams which can be seen in student learning outcomes in cycle I only reaching 58.5% so it does not meet the KKM and increases in cycle II to 84 .5% so that it meets the KKM criteria